The Influence of Consumer Behavior and Trust on Purchasing Decisions at NewYorkArt Medan - Halim, Cheviria; Pesta Gultom; Hommy Dorothy Ellyany Sinaga (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2023)
The purpose of this research is to analyze the influence of consumer behavior and trust on purchasing decisions at NewYorkArt Medan. The research method in this research is a quantitative research method using a questionnaire as a data collection technique. The population in this research is all consumers who made purchases at New York Art Medan as many as 216 consumers in 2022 and using the Slovin formula obtained 140 respondents. The research results show that consumer behavior have influences on purchasing decisions and trust have influences on purchasing decisions. Simultaneously shows that consumer behavior and trust influence purchasing decisions. Consumer behavior and trust can explain purchasing decisions by 49.7% and the remaining 50.3% is influenced by other factors originating from outside this research model such as service quality and brand image.